Outcome Based Assessment:A Case Study on Undergraduate Course on Control Systems - Kurian, Ciji Pearl; George, V. I.; George, Anna Merine; Kini, Savitha G. (Journal of Engineering Education Transformations, 2016)
The Outcome Based Assessment (OBA) has been one of the major concerns of most engineering departments in India since the National Board of Accreditation (NBA) has made it compulsory towards programme accreditation. Implementation of the OBA may not be an easy task when considering the mapping of the course outcome (CO) to Programme Outcomes (PO). This paper describe the analysis process of the CO and PO attainment for an undergraduate course on control systems, a subject, which is offered to 3rd year students of Electrical & Electronics Engineering at Manipal University. Two methods are incorporated for the assessment of course outcomes and PO attainment (1) direct measurement, and (2) indirect measurement. As a whole, this paper gives complete procedure and a sample analysis for Outcome Based Assessment starting from course curriculum development to its outcome attainment based on defined criteria’s.